Considering Ethics in Agricultural Experimental Research with Special Mention to Agricultural Biotechnology Research - Danarsi Diptaningsari; Edhi Martono (Universitas Gadjah Mada, 2021)
Ethics in experimental research equals scientific integrity, a notion principle particularly stressing honesty while implementing discipline concepts on what is excellent and terrible. Some moral responsibility is defined through specifically agreed standards in doing experimental research. Ethics of experimental research in agriculture involves all activities done before, during, and after the study, consisting of personal, research, and social ethics. Ethical code and policy include, but are not limited to, honesty, objectivity, integrity, carefulness, openness, intellectual right recognition, confidentiality, responsible publication, social responsibility, competency, legality, and protecting research object/subject (plant, animal, human) from possible unfair manipulation. One development triggering the controversy of agriculture’s experimental ethics is the progress of agricultural biotechnology which resulted in genetic engineering products. Rules, regulations, and laws concerning the use and development of genetic engineering in agriculture to avoid adverse effects of these products, such as rising environmental hazards, increasing human health degradation, and unfair economic competition, should be considered and implemented.